A novel field for possible use in medical impedance tomography - Calderwood, J. H.; Mognaschi, E. R. (Journal of medical engineering & technology, 1998)
A single-phase electrical supply is normally used to energize the electrodes of the belt worn by the subject for medical impedance tomography. in the process, the supply is switched from one adjacent pair of electrodes to the next, so that all such pairs are energized in turn. However, if a three-phase voltage of constant amplitude were to be employed, with electrodes uninterruptedly connected to the lines of the supply in phase sequence around the periphery, and the current flowing through each electrode were to be simultaneously measured, it will be shown that, in principle, data of higher utility would result. This paper examines that possibility, and considers the field spatial harmonics arising in consequence of the electrode geometry. Expressions are obtained for the magnitude of those harmonics in close proximity to the surface of the belt, from which the spatial harmonic components of the applied field at deeper levels can be calculated. It is shown that if bar electrodes are employed, the spatial harmonic composition of the field is critically dependent on the ratio of the width of the electrodes to the width of the gaps between them.